Relationship between pharmacokinetics and pharmacodynamics of clopidogrel in patients undergoing percutaneous coronary intervention: comparison between vasodilator‐stimulated phosphoprotein phosphorylation assay and multiple electrode aggregometry. (29th January 2016) - Danese, E.; Fava, C.; Beltrame, F.; Tavella, D.; Calabria, S.; Benati, M.; Gelati, M.; Gottardo, R.; Tagliaro, F.; Guidi, G. C.; Cattaneo, M.; Minuz, P.
Abstract : Essentials The reliability of platelet tests as markers of the variable bioavailability of clopidogrel is not yet defined. Kinetics of clopidogrel active metabolite (CAM) and platelet response were studied in ischemic heart disease. CAM plasma maximum concentration (Cmax ) predicted vasodilator‐stimulated phosphoprotein (VASP‐P). Timely performed VASP‐P, not an aggregation‐based test, may be a surrogate for clopidogrel bioavailability. Summary: Background: The high inter‐individual variability in the inhibition of platelet function by clopidogrel is mostly explained by high variability in its transformation to an active metabolite (CAM). Objective: We investigated the relations between pharmacokinetics and pharmacodynamics of CAM by comparing two methods of platelet function. Methods: We enrolled 14 patients undergoing percutaneous coronary interventions for non‐ST‐segment elevation acute coronary syndrome or inducible myocardial ischemia. Plasma concentrations of clopidogrel and CAM, phosphorylation of vasodilator‐stimulated phosphoprotein (VASP‐P), expressed as a platelet reactivity index (PRI) and whole‐blood platelet aggregation (multiple electrode aggregometer, MEA) were measured before and after a 600‐mg clopidogrel loading dose (nine time‐points) and before and after 75‐mg maintenance doses on days 2, 7 and 30. Results: Plasma concentrations of clopidogrel and CAM were highly variable. CAM reached maximal concentration ( C max ) (median, 110.8 nm ; range, 41.9–484.8) 0.5–2 h after the loading dose. A sigmoid dose‒response curve defined the relations between CAM C max and PRI after 3 to 24 h (IC50, 459.6 nm; 95% confidence interval, 453.4–465.7; R 2 = 0.82). PRI was unchanged from baseline in patients with the lowest CAM C max (< 83 nm, n = 7), indicating low sensitivity of VASP‐P. PRI values were also predicted by CAM C max at days 2, 7 and 30. Platelet aggregation measured by MEA did not show significant relations with either PRI or with CAM pharmacokinetics at any time‐point. Conclusions: After 600 mg clopidogrel, VASP‐P, but not whole‐blood platelet aggregation measured by MEA, is almost entirely predicted by CAM C max . VASP‐P could be useful in studies aimed at investigating relations between CAM bioavailability and clinical events.